Recommendations for Ecotourism Potential Development of Cidanti Lake, Gunungsari Village, Cikatomas Subdistrict, Tasikmalaya Regency, West Java Province (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Gunungsari Village, Cikatomas District, Tasikmalaya Regency is a village that has natural beauty with the presence of Situ Cidanti. The natural beauty of Situ Cidanti has the potential to become an ecotourism destination. Ecotourism is a form of tourism that prioritizes and supports nature conservation efforts. However, this ecotourism potential has yet to be utilized optimally by residents. Therefore, it is necessary to prepare a recommendation document containing programs that can become a reference for developing the ecotourism potential of Situ Cidanti in Gunungsari Village. The recommendation document was created by the community service team from Siliwangi University. The contents of the recommendation document for developing Situ Cidanti's ecotourism potential consist of creating a location planning program and establishing local communities as an ecotourism management team that continues to protect existing natural resources. Apart from that, an important thing that needs to be done is branding through digital marketing, such as updating the village's official website, YouTube, and Facebook channels, as well as updating the website and social media accounts already available. This ecotourism development program aims to provide socio-economic benefits by involving citizen participation. It is hoped that Situ Cidanti Ecotourism can attract visitors, especially from outside Gunungsari Village, while preserving nature. Hopefully, these visitors can increase the economic activities of residents involved in UMKM in Gunungsari Village. Therefore, the expected target of this community service is that village officials as service partners can implement programs based on the recommendation documents that have been prepared with sustainable principles. Implementing the program in this document is hoped to make Situ Cidanti a leading ecotourism destination in Tasikmalaya Regency.